PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Handayani, Lussy Andrivia; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of good corporate governance and company size on financial performance in banking companies listed on the Indonesia Stock Exchange. The ratio of good corporate governance that is used as an independent variable is managerial ownership, the composition of the independent board of commissioners and the audit committee. The company size ratio used as an independent variable is the logarithm of natural total assets (in total assets). While the financial performance ratio used as the dependent variable is return on equity. The method used to observe the effect of good corporate governance and company size on financial performance using simple linear regression and multiple linear regression.The data used in this study are secondary data, financial reports and annual report annual reports. The data is listed on the Indonesia Stock Exchange (IDX) for 5 years from the period 2012-2016. Sampling was done by purposive sampling, 9 companies were used. Data analysis using simple linear regression, multiple linear regression, t test, f test and test coefficient of determination. Data analysis using simple linear regression and multiple linear regression with SPSS 25.The results of this study indicate that the variables of good corporate governance partially (t test) affect the financial performance, while the variable size of the company influences the financial performance of banking companies listed on the Indonesia Stock Exchange. The simultaneous test results (F) show the influence of good corporate governance and company size on financial performance in banking companies listed on the Indonesia Stock Exchange. Keywords: Good Corporate Governance, Company Size, Financial Performance